2020
DOI: 10.2147/jpr.s242568
|View full text |Cite
|
Sign up to set email alerts
|

<p>Analgesic Efficacy of Erector Spinae Plane Block Compared with Intrathecal Morphine After Elective Cesarean Section: A Prospective Randomized Controlled Study</p>

Abstract: Background: We aimed to assess the efficacy of ultrasound-guided bilateral erector spinae plane block (ESPB) compared to intrathecal morphine (ITM) for analgesia after elective cesarean delivery under spinal anesthesia. Methods: In total, 140 parturients scheduled for elective cesarean section under spinal anesthesia were randomly allocated into two equal groups. The ESPB-group received 10 mg hyperbaric bupivacaine intrathecally through spinal anesthesia, followed by an ESPB at the ninth thoracic transverse pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 27 publications
2
27
0
4
Order By: Relevance
“…Two studies recently evaluated the erector spinae plane block (ESP) compared with TAP block and intrathecal morphine and in both studies the ESP block improved analgesia [122,123].…”
Section: Local and Regional Analgesia Techniquesmentioning
confidence: 99%
“…Two studies recently evaluated the erector spinae plane block (ESP) compared with TAP block and intrathecal morphine and in both studies the ESP block improved analgesia [122,123].…”
Section: Local and Regional Analgesia Techniquesmentioning
confidence: 99%
“…Erector spinae plane block is another possibility of ultrasound-guided analgesia as it produces satisfactory pain reduction when compared with intraspinal morphine and TAP block [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Hamed et al [38] compared IT morphine at a dose of 100 μg with the execution of the ESP block without IT opioid administration, in 140 studied patients no statistically significant difference was found in the perception of pain during the 24 hours after surgery, both at rest and with Valsalva maneuvers (cough), or in reducing the consumption of postoperative opioid analgesics. However, the study reports methodological limitations that could be biasing the result, but the usefulness is emphasized as a multimodal analgesic management in obstetric patients.…”
Section: Erector Spinae Plane Blockmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have compared the analgesia from a single-shot erector spinae plane (ESP) block to that of intrathecal morphine 4 or a transversus abdominis plane block. 5 These studies demonstrated that ESP block (which is easy to perform, even in obese 6 and pregnant patients) provides both somatic and visceral pain control, 7 likely through both neural blockade and central inhibition from direct spread of local anesthetic to the paravertebral or epidural space.…”
Section: Pain Control After Cesarean Section: Continuous Bilateral Erector Spinae Plane Blockmentioning
confidence: 99%